An investigation of the influence of co-morbid anxiety on functional connectivity changes in the MIA model of OA pain - Lillywhite, Amanda (2020)
Background: Pain, although universally experienced and adaptive, can negatively impact daily functioning and quality of life when it becomes chronic. Osteoarthritis is one of the most commonly experienced chronic pain conditions, with a huge personal and societal impact. The treatment of OA can be challenging and is complicated by a number of frequently experienced co-morbid conditions.